Księgi Kronik (1-2 Krn) w Qumran - Parchem, Marek (Collectanea Theologica, 2020)
The review of the presence of the Books of Chronicles (1–2 Chronicles) in the Dead Sea Scrolls shows that they did not enjoy any significant interest and popularity among the members of the Qumran community. This is testified by the fact that there is only one copy which contains a text which is very similar, however not identical, to the biblical one (4Q118). As the 4Q118 document has survived in a highly fragmentary state, its identification is not certain. Although some scholars believe that it can be regarded as the copy of the biblical text which differs from the Masoretic version, it seems more reasonable to view this document as a paraphrase or a parallel text of 1–2 Chronicles. That the Books of Chronicles were of little interest to the Qumran dwellers is also confirmed by the lack of any direct quotations in the non-biblical documents. The sparse allusions in 4Q522 and 4Q252 need to be assessed just as a probable reference to 1–2 Chronicles. On the other hand, in the case of the Temple Scroll (11QT) and the Prayer of Manasseh (4Q381 fr. 33 and 35, lines 8-11) there are some relations between these documents and the Books of Chronicles, but it should be noted that neither of the works is the composition of the Qumran community itself.